Previous school experience and university life (Praxis Educativa, 2016)
The main purpose of this paper is to share research results. These are about the reconstruction that students do on their previous school experiences and how they contrast them with the changes in their university life. The central problem was linked to the need to know the characteristics of young people who are in fact living at the stage of university. We have as a goal to show some of their psychosocial references in order to identify issues related to the experiences in this new step and their ways of action on the construction of their institutional place. The research was conducted in 2014. It is a mixed methodological approach, because we gave a questionnaire with closed and open questions, but also, we took individual and group interviews. The population consisted of students who were enrolled in their second year of Chemical and Veterinary Sciences at the Catholic University of Córdoba.
Keywords: students; school experiences; university stage